Phosphatidylinositol 3-kinase regulatory subunit 1 and phosphatase and tensin homolog as therapeutic targets in breast cancer - Ebubekir Dirican; Mustafa Akkiprik (Tumor Biology)
Breast cancer is the most commonly diagnosed cancer among women in Turkey and worldwide. It is considered a heterogeneous disease and has different subtypes. Moreover, breast cancer has different molecular characteristics, behaviors, and responses to treatment. Advances in the understanding of the molecular mechanisms implicated in breast cancer progression have led to the identification of many potential therapeutic gene targets, such as Breast Cancer 1/2, phosphatidylinositol 3-kinase catalytic subunit alpha, and tumor protein 53. The aim of this review is to summarize the roles of phosphatidylinositol 3-kinase regulatory subunit 1 (alpha) (alias p85α) and phosphatase and tensin homolog in breast cancer progression and the molecular mechanisms involved. Phosphatase and tensin homolog is a tumor suppressor gene and protein. Phosphatase and tensin homolog antagonizes the phosphatidylinositol 3-kinase/AKT signaling pathway that plays a key role in cell growth, differentiation, and survival. Loss of phosphatase and tensin homolog expression, detected in about 20%–30% of cases, is known to be one of the most common tumor changes leading to phosphatidylinositol 3-kinase pathway activation in breast cancer. Instead, the regulatory subunit p85α is a significant component of the phosphatidylinositol 3-kinase pathway, and it has been proposed that a reduction in p85α protein would lead to decreased negative regulation of phosphatidylinositol 3-kinase and hyperactivation of the phosphatidylinositol 3-kinase pathway. Phosphatidylinositol 3-kinase regulatory subunit 1 protein has also been reported to be a positive regulator of phosphatase and tensin homolog via the stabilization of this protein. A functional genetic alteration of phosphatidylinositol 3-kinase regulatory subunit 1 that results in reduced p85α protein expression and increased insulin receptor substrate 1 binding would lead to enhanced phosphatidylinositol 3-kinase signaling and hence cancer development. Phosphatidylinositol 3-kinase regulatory subunit 1 underexpression was observed in 61.8% of breast cancer samples. Therefore, expression/alternations of phosphatidylinositol 3-kinase regulatory subunit 1 and phosphatase and tensin homolog genes have crucial roles for breast cancer progression. This review will summarize the biological roles of phosphatidylinositol 3-kinase regulatory subunit 1 and phosphatase and tensin homolog in breast cancer, with an emphasis on recent findings and the potential of phosphatidylinositol 3-kinase regulatory subunit 1 and phosphatase and tensin homolog as a therapeutic target for breast cancer therapy.